Identification of a potent Angiotensin-I converting enzyme inhibitory peptide from Black cumin seed hydrolysate using orthogonal bioassay-guided fractionations coupled with in silico screening. (August 2020) - Sutopo, Christoper C.Y.; Sutrisno, Aji; Wang, Li-Fei; Hsu, Jue-Liang
Graphical abstract: Highlights: First ACE inhibitory peptide identified from Black Cumin Seed Hydrolysate . ACEI peptide was screened and identified using two bioassay-guided fractionations coupled with de novo peptide sequencing. VTPVGVPKW is a true inhibitor as well as a non-competitive inhibitor of ACE. Abstract: Black cumin ( Nigella sativa ) seed protein (BCSP) was individually hydrolyzed with pepsin, trypsin, and α-chymotrypsin. After ultrafiltration, the α-chymotrypsin hydrolysate (< 3 kDa) exhibited the highest ACE inhibitory (ACEI) activity with an IC50 value of 34.4 ± 1.5 μg/mL. This hydrolysate was orthogonally fractionalized using reversed-phase high-performance liquid chromatography (RP-HPLC) and strong cation exchange (SCX) chromatography, and the most active RP-HPLC and SCX fractions (F7 and H4, respectively) were individually screened out by ACEI assay. These two fractions were analyzed with liquid chromatography-tandem mass spectrometry (LC–MS/MS) followed by automated de novo peptide sequencing, and totally 43 ACEI candidate peptides were identified. Three overlapping peptides (VTPVGVPKW, VVTPVGVPKW, and LVLTL) were simultaneously contained in both fractions, and VTPVGVPKW (VW-9) was speculated as to the most potent ACEI peptide based on the in silico analysis. Synthetic VW-9 was used to confirm the identity, and a remarkable IC50 value of VW-9 (1.8 ± 0.09 μM) was determined. Preincubation and inhibition mechanism studies indicated that VW-9 was a true inhibitor as well as a non-competitive inhibitor on ACE, which was further illustrated with the molecular docking simulation. Our study revealed that the application of VW-9 to antihypertensive products is promising.